2017
DOI: 10.1017/s1041610217001442
|View full text |Cite
|
Sign up to set email alerts
|

Drug-related problems in community-dwelling primary care patients screened positive for dementia

Abstract: Background:Older people have a higher risk of drug-related problems (DRPs). However, little is known about the prevalence of DRPs in community-dwelling people who screened positive for dementia. Our study aimed to determine (1) the prevalence and types of DRPs and (2) the socio-demographic and clinical variables associated with DRPs in people screened positive for dementia in primary care.Methods:The Dementia: life- and person-centered help in Mecklenburg-Western Pomerania (DelpHi-MV) study is a general practi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
60
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(64 citation statements)
references
References 39 publications
3
60
0
1
Order By: Relevance
“…Of these, 17 were excluded due to having: an irrelevant setting that is not primary care, irrelevant interventions that were only addressing medication errors instead of reporting on drug related adverse events and describing only qualitative aspects of medication safety. The final search yielded a total of 19 citations for inclusion in this review, with two abstracts and 17 full papers [26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44]. A protocol detailing the methodology for the current review was followed [23].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Of these, 17 were excluded due to having: an irrelevant setting that is not primary care, irrelevant interventions that were only addressing medication errors instead of reporting on drug related adverse events and describing only qualitative aspects of medication safety. The final search yielded a total of 19 citations for inclusion in this review, with two abstracts and 17 full papers [26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44]. A protocol detailing the methodology for the current review was followed [23].…”
Section: Resultsmentioning
confidence: 99%
“…28, 42]. Overall, the incidence of ADR reported in the studies ranged between 6% and up to 80% in some cases [29,44].…”
Section: Adrs Incidencesmentioning
confidence: 99%
See 2 more Smart Citations
“…The role of pharmacists in management of AD is increasingly recognized, which includes recognizing early symptoms of AD, referring AD patients to seek for timely diagnosis and treatment, identifying potential ADRs of pharmacological treatment, and educating and providing counseling to the AD patients and caregivers. For example, findings from a study on multi-disciplinary dementia care services conducted in Germany revealed that pharmacists are adapt in identifying problems related to drug administration, adherence, and drug interaction among patients with dementia (Wucherer et al, 2017 ). Meanwhile, in the United Kingdom, a trial targeting people with dementia initiated on anti-psychotics demonstrated that pharmacist-led medication review successfully limited the prescribing of anti-psychotics to people with dementia because of the increased risk of ADRs (Child et al, 2012 ).…”
Section: Discussionmentioning
confidence: 99%